Leading education systems - Duignan, P. A.; Brown, Stephen (Emerald Group Publishing, 2021)
As the once-in-a-lifetime stimulus of a pandemic creates the opportunity for change, this ground-breaking and timely edited text is a must-have springboard for the re-imagination of education system leadership. How can education stakeholders act in collaboration to lead us into a new and different age?